Parâmetros de compactação com aterros experimentais para um solo da cidade de Pau dos Ferros - Limeira, Emilyanno Saraiva (Universidade Federal Rural do Semi-Árido, 2018)
The compacting of the soils has always accompanied the society, is present in the present day as one of the main applications to great works of the civil engeneering. The objective of this work was to verify the efficiency of the study of compaction parameters through the use of experimental landfills, applied to the soil of the city of Pau dos Ferros-RN located 392 km from Natal capital of Rio Grande do Norte. The present study was divided into two stages, the first one being associated to a laboratory study, where granulometry tests were carried out, for better soil characterization, plasticity assay, specific mass and compaction in order to serve as parameters for the accomplishment of the second stage, the second part was characterized by the application of experimental landfills which is a solution for the study of the compaction carried out in the field, in each landfill made, a sand flask test was carried out in order to obtain the degree of compaction, in then the analysis of these data was done so that the comparison between parameters of high degree of importance could be made. Thus, it was observed that for a given number of strokes equal to 80 the decrease in the degree of compression occurred, one of the probable motives for the event is that from a certain point the material acquires a considerable stiffness, causing a disturbance of the structure and ground grinding leading to a reduction in the degree of compaction.
Keywords: Plasticidade; Frasco de areia; Granulometria; ENGENHARIAS::ENGENHARIA CIVIL